2020
DOI: 10.1155/2020/8346981
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy Detects Peters’ Anomaly and Rieger’s Anomaly in Infants

Abstract: Aim. Congenital corneal opacities (CCOs) are the major causes of early visual deprivation in infants. Balloon ultrasound biomicroscopy (UBM) examination is an effective method to diagnose CCO. However, whether it is suitable for children examination is still unknown. Methods. 26 Peters’ anomaly (PA) or Rieger’s anomaly (RA) infants with congenital corneal opacities (CCO) (40 eyes) underwent UBM examinations to study their imaging features. Results. Based on the results, they were divided into UBM Dx-Type I: De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…2011; Chen et al. 2020). Advantage of this technique is that it enables examination in any position (Kosmala et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011; Chen et al. 2020). Advantage of this technique is that it enables examination in any position (Kosmala et al.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies included in this review, this UBM technique was used (Dietlein et al 2000;Tandon et al 2017;Shi et al 2018Shi et al , 2020. Alternatively, the UBM probe can be covered with a sterile balloon filled with distilled water and placed directly on the eye (Mireskandari et al 2011;Chen et al 2020). Advantage of this technique is that it enables examination in any position (Kosmala et al 2018).…”
Section: Ubm Techniques In Childrenmentioning
confidence: 99%
“…3 The UBM is an invaluable diagnostic and prognostic tool in evaluating anterior segment pathology including aniridia, iridolenticular adhesions, anterior chamber angle structures, and limbal dermoids. [54][55][56][57] In their series, Nischal and colleagues reported that UBM diagnosis agreed 100% with the histologic diagnosis, while 5/13 (38%) of cases were clinically misdiagnosed as sclerocornea (2), keratectasia (1), and congenital glaucoma (2). Respectively, Peter anomaly (first 3 cases) and congenital corneal dystrophy (last 2 cases) were diagnosed using UBM and confirmed histologically.…”
Section: Ubmmentioning
confidence: 97%
“…Typically, this requires a high level of cooperation from the patient with at least topical anesthestic drops or sedation 3. The UBM is an invaluable diagnostic and prognostic tool in evaluating anterior segment pathology including aniridia, iridolenticular adhesions, anterior chamber angle structures, and limbal dermoids 54–57…”
Section: Introductionmentioning
confidence: 99%
“…The most common topic of literature evaluating use of UBM in pediatric subjects with corneal pathology was congenital corneal opacities (CCO), including but not limited to the spectrum of anterior segment dysgenesis. Key findings from these studies include: (1) AS-OCT and UBM can be used interchangeably for corneal thickness and depth measurements in patients with CCO [53], (2) in cases of CCO with penetrating keratoplasty histopathological correlation, UBM diagnosis was correct 100% of cases while clinical diagnosis prior to UBM was correct in 62% of cases [54], (3) UBM informs genotype-phenotype correlations [54], (4) UBM assisted in both diagnosis and treatment decisions for CCO [55][56][57][58][59]. Other pediatric corneal diseases evaluated using UBM includes keratoconus (acute hydrops [60,61], and intrastromal ring implantation [62]), and deep anterior lamellar keratoplasty (DALK) outcomes and indications [63].…”
Section: Corneamentioning
confidence: 99%